A REVIEW: TERAHERTZ SPECTROSCOPY AS A VIABLE DYNAMIC TOOL FOR PROTEIN AND ORGANIC MOLECULES CHARACTERIZATION - Zakaria, Hidayatul Aini (Malaysian Journal of Science, 2015)
THz spectroscopy is a relatively new spectroscopic method in which the THz useful range of frequencies is from 300 cm-1 down to 3 cm-1, a spectral region unachievable by FTIR spectroscopy. Multiple resonances in the absorption spectra of organic molecules exist in the THz range around 0.1–10 THz (3 to 300 cm-1) where these resonances arise from electromagnetic wave interaction of the THz source with the low-frequency, and hence large- scale, vibrational modes within the organic macromolecules. These major vibrational modes correspond to the quaternary or overall structure of macromolecules. The concerted motion of protein structure can also be investigated by THz spectroscopy, which enables both energy and momentum transfer at the picosecond time scale. The short bursts of far-IR radiation in an ultra-fast time scale in THz spectroscopy allow researchers to study the dynamic processes of various materials for a large variety of applications. This review paper discusses the probability of utilizing THz spectroscopy as a probe to determine the intermolecular structures of macromolecules as well as basic technical knowledge in THz spectroscopy. Keywords:Terahertz, spectroscopy, vibrational, proteins, organic molecules